Ammonium/nitrate ratios in acid and alkaline solutions nutritious blueberry - Crisóstomo Crisóstomo, María Natividad; Hernández Rodríguez, Ofelia Adriana; López Medina, José; Manjarrez Domínguez, Carlos; Pinedo-Alvárez, Alfredo (Revista Mexicana de Ciencias Agrícolas, 2018)
The aim of this study was to evaluate the growth of cranberry (Vaccinium sp.) Cv. Biloxi during the vegetative phase, application of NH4 + ratios /NO3 - in nutrient solutions of acid and alkaline Steiner through the variables: plant height, shoot length and nutrient concentration in leaf tissue. The experiment was conducted under a design in randomized complete block with ten treatments and twelve repetitions, the analysis of variance of the variables were performed using the Proc GLM of SAS version 8.2, for the mean comparison test Tukey (p< 0.05). Plants showed increased growth when the NH4 +/NO3 - ratio was 0/100 and pH of 5, while a ratio NH4 +/NO3 - 50/50 favored the length and the size of sheets only during week1 without showing significant in the later stages. Regarding the nutrient concentrations in the leaf tissue, a ratio NH4 +/NO3 - 100/0 and pH 5 favored a higher content of Ca and Mg (2.02 and 0.21%, respectively) as well as Mn and Zn (300 and 9.75 mg L-1, respectively), but in the case of K, the higher leaf content of this element (4.97%) was for plants with a NH4 +/NO3 - ratio of 0/100 and pH 6. These results suggest that cranberry cv. Biloxi is capable of taking both N as NH4 + and NO3 - during the vegetative phase.
Keywords: Steiner; pH; ammonium/nitrate ratio; nutrient solution